Political Will Pemerintahan Kabupaten Banyuasin dalam Meningkatkan Industri Pangan di Kecamatan Tungkal Ilir - Luthfi Akhiri Ramadhan; Izomiddin Izomiddin; Yulion Zalpa (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
The growth of the food industry means an increase in supply which aims to increase the output of domestic food commodities. Food is the most basic need in human life. One of the areas where the food industry in Indonesia is developing is Banyuasin Regency in South Sumatra, as evidenced by the award received by the Regent of Banyuasin (Askolani) namely the Indonesian Self-Help Food Security Category 2020. In Tungkal Ilir sub-district, it is a sub-district that excels in plantation and food crop sector commodities, he also added that food crop commodities in Tungkal Ilir sub-district are included in IP200 or two harvests in one year. Of course, from this award there is a strong political will from the Regency Government. The method used in this study is a qualitative and descriptive method, which is a field research, the data source used in this study is the main data, namely interviews, for data analysis techniques the author uses three stages, namely, data reduction, data presentation, and drawing conclusions. The theory used is the theory of political willingness by Brinkerhoff which is associated with the political will of the Banyuasin district government. This theory is able to analyze the political will of the Banyuasin government in improving the food industry in Tungkal Ilir sub-district. The results of this study indicate that the political will of the Banyuasin district government in improving the food industry in Tungkal Ilir sub-district has various ways to do it, such as spending on initiatives in the form of receiving Field Extension Officers (PPL) for each village, then with the help of Production Facilities (SaProdi). Followed by the implementation of political policies to increase food production such as the SeRaSi policy and also the OpLa policy intended for the Tungkal Ilir sub-district and Indonesia as a whole. Keywords: Political Will, Government, Food